Desarrollo profesional hacia el dominio de la implantación tecnológica como consultoría de negocio - Urquiza Cabrera, Javier Jesus (2023)
As a graduate of Systems Engineering from the University of Lima, during my professional career I have participated in various technological initiatives and projects that have allowed me to apply all the knowledge acquired during my academic training at the university. During the first years I participated in operational and mainly technical responsibility roles, while I also acquired and developed my project management skills and managerial skills. The main areas of application in which I have been able to develop and apply my knowledge have been regulatory adaptation for regulated entities, technological renewal of business processes, risk modeling, management of technological development teams, technological implementation strategy and, as part of my growth in Management Solutions, the commercial monitoring of the core competence of the core competence of Risk, Credit and Capital. As indicated above, the professional development that I detail in this report demonstrates the path and work experiences that have allowed me to successfully achieve and apply technological implementation in the Management Solutions’ clients with whom I have worked, ensuring a correct deployment of technical skills, work team management and, above of all, full satisfaction on the part of the client and the users with the product and services delivered.